Inter relationship of sympathetic reflex response and oxidative stress in polycystic ovary syndrome - Akhter, Ayesha; Mostafa, Musfika; Sultana, Shamima; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2022)
Background: Polycystic ovary syndrome (PCOS) is a very common reproductive endocrine disorder. Altered cardiovascular autonomic modulation and oxidative stress may predispose PCOS patients to cardiac events in the long term. Objective: To assess the relationship between sympathetic autonomic reactivity and oxidative stress in patients with polycystic ovary syndrome. Methods: This cross-sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from September 2018 to August 2019 on 35 newly diagnosed obese (BMI ≥25kg/m2) PCOS patients aged 20-35 years. Age and BMI matched 35 apparently healthy subjects were also enrolled. Two noninvasive conventional autonomic function tests, such as systolic blood pressure (SBP) fall during active standing and diastolic blood pressure (DBP) rise during sustained handgrip were conducted on all subjects for evaluation of sympathetic reactivity. For assessment of oxidative stress, plasma malondialdehyde level as oxidant and plasma catalase level as antioxidant were measured in all subjects by spectrophotometry. For statistical analysis Independent sample “t” test, Pearson’s correlation test and multiple regression analysis were done. Results: In this study PCOS patients had significantly higher resting heart rate, SBP and DBP than healthy control (p<0.01). Fall of SBP during standing was significantly lower (p<0.05) while rise of DBP during sustained handgrip was significantly higher (p<0.05) in PCOS compared to healthy control. Plasma catalase level was significantly lower (p<0.01) and plasma malondialdehyde level significantly higher (p<0.001) in PCOS in comparison to healthy control. On correlation analysis, rise of DBP showed significant negative correlation (p<0.05) with plasma catalase level in PCOS. On multiple regression analysis rise of DBP showed significant negative (p<0.01) association with plasma catalase and significant positive (p<0.01) association plasma malondialdehyde in PCOS. Conclusion: Based on these results it is concluded that measures of sympathetic reactivity were related to oxidative stress in PCOS. J Bngladesh Soc Physiol 2021;16(1): 61-69